Assessment of level-walking aperiodicity - Pecoraro, Fabrizio (BioMed Central, 2006)
BACKGROUND: In gait analysis, walking is assumed to be periodic for the sake of simplicity, despite the fact that, strictly speaking, it can only approximate periodicity and, as such, may be referred to as pseudo-periodic. This study aims at: 1) quantifying gait pseudo-periodicity using information concerning a single stride; 2) investigating the effects of walking pathway length on gait periodicity; 3) investigating separately the periodicity of the upper and lower body parts movement; 4) verifying the validity of foot-floor contact events as markers of the gait cycle period. METHODS: Ten young healthy subjects (6 males, 23 ± 5 years) were asked to perform various gait trials, first along a 20-m pathway that allowed reaching a steady-state condition, and then along an 8-m pathway. A stereophotogrammetric system was used to reconstruct the 3D position of reflective markers distributed over the subjects' body. Foot contact was detected using an instrumented mat. Three marker clusters were used to represent the movement of the whole body, the upper body (without upper limbs), and the lower body, respectively. Linear and rotational kinetic, and gravitational and elastic potential "energy-like" quantities were used to calculate an index J(t) that described the instantaneous "mechanical state" of the analysed body portion. The variations of J(t) in time allowed for the determination of the walking pseudo-period and for the assessment of gait aperiodicity. RESULTS: The suitability of the proposed approach was demonstrated, and it was shown that, for young, healthy adults, a threshold of physiological pseudo-periodicity of walking at natural speed could be set. Higher pseudo-periodicity values were found for the shorter pathway only for the upper body. Irrespective of pathway length, the upper body had a larger divergency from periodicity than the lower body. The error that can be made in estimating the gait cycle duration for the upper body from the heel contacts was shown to be significant. CONCLUSION: The proposed method can be easily implemented in gait laboratories to verify the consistency of a recorded stride with the hypothesis of periodicity.